Cholinetrase concentration in the blood of three types of cattle raised on land exposed to Organophosphates - Ali Harokan; Totong Kamaluddin; Daniel Saputra; Nurhayati Damiri (Program Pascasarjana Universitas Sriwijaya, 2021)
Organophosphate pesticides are one of the causes of contamination in animal feed. The cholinesterase enzyme test is used to diagnose toxic exposure due to organophosphate pesticides. Quantitative research with survey design using cross sectional design using 35 samples of cows. The study was conducted in March - September 2020. Concentration measurement on cholinesterase enzyme concentrations of blood plasma used the biosystem A15 DGKC-Colorimetric Kinetic method. This study aims to evaluate the concentration of the enzyme cholinesterase as a marker of organophosphate poisoning in cattle. Blood samples were collected from the ventrolateral neck veins of male and female cattle aged 1-7 years and collected from local cattle in the Ogan Ilir area. The results showed that the cows raised in breeders were exposed to organophosphate pesticides as indicated by a decrease in the concentration and levels of the cholinesterase enzyme in the plasma of female cows. Cholinestrase enzyme levels in female cows were 0.20 ± 0.067 U / ml and bulls were 0.27 ± 0.183 U / ml. The highest concentration of cholinesterase enzyme levels occurred in cows aged 2 years, namely 0.25 ± 0.34 U / ml and the lowest was in cows aged 7 years, namely 0.12 ± 0.04 U / ml.